Association of prednisone and antinuclear antibodies with pregnancy outcomes in women with unexplained recurrent pregnancy loss. Issue 3 (19th January 2021) - Sun, Si; Li, Congcong; Kou, Xi; Chen, Chao; Guo, Feng; Zhao, Aimin
Abstract: Objective: To investigate the therapeutic role of prednisone in patients having unexplained recurrent pregnancy loss (URPL) with positivity of antinuclear antibodies (ANA) and the relationship between ANA titers, prednisone, and pregnancy outcomes. Methods: We included 202 women diagnosed as having URPL with positive ANA at titer of 1:80 or more. Among them, 159 patients receiving prednisone plus aspirin were included as group PA and the remaining 43 patients prescribed aspirin only served as group A. Live birth rates were considered as the primary outcome. Incidence rates of pregnancy complications and outcomes of the newborns were also compared. Additionally, the association between live birth and major clinical variables was studied. Results: Live birth rates were comparable between the two groups (93.1% versus 83.7%, P = 0.107). No significant differences were observed regarding the incidence rates of adverse pregnancy outcomes, other pregnancy complications and the fetal outcomes. Alteration of ANA titers after pregnancy compared with pre‐conception results was the only significant variable associated with live birth. Conclusion: Prednisone plus aspirin did not show improved therapeutic effects over aspirin alone in URPL patients with positive ANA. Variation of ANA titers was found to be a prognostic indicator of pregnancy outcomes in these patients. Synopsis: In unexplained recurrent pregnancy loss patients with positive antinuclear antibodies (ANA), prednisone plus aspirin do not improve therapeutic effects over aspirin alone. ANA titer variation is prognostic of pregnancy outcomes.